(untitled) (Annals of Medical Research, 2023)
Aim: The negative effects of the COVID-19 pandemic on a global scale and the resulting changes in daily life habits have significantly influenced the growth and development of adolescents. Adolescents have been deeply affected in physical, mental, and social aspects, both by COVID-19 itself and its psychological impact. This study aims to assess the sleepiness, social anxiety, and blood pressure status of adolescents during the COVID-19 pandemic. Materials and Methods: A total of 412 adolescents in the 6th, 7th, and 8th grades participated in this descriptive cross-sectional study. Data was collected using a questionnaire consisting of socio-demographic characteristics and questions related to COVID-19, the Cleveland Adolescent Sleepiness Scale (CASS), and the Social Anxiety Scale for Adolescents (SAS-A). The students’ blood pressure was measured in a classroom setting. Results: It was determined that 23.1% of the adolescents participating in the study had experienced COVID-19, and 42.7% of them had family members who had also had COVID-19. It was found that adolescents who had not experienced COVID-19 reported higher levels of emotions such as fear, distress, and sadness (p<0.05). A positive correlation was identified between the sleepiness status of adolescents and their social anxiety (r = 0.368, p = 0.000). The systolic blood pressure of adolescents was found to be 7.3% high-normal and 9.7% high. Diastolic blood pressure was determined to be 3.6% high-normal and 1.7% high. A significant difference in diastolic blood pressure was identified between those who had experienced COVID-19 and those who had not (p<0.05). Conclusion: According to the results of the study, it is observed that adolescents experience moderate levels of sleepiness and social anxiety. Hence, adolescents have been affected psychologically and physiologically during the COVID-19 pandemic. The short and long-term effects of the pandemic on adolescents should be monitored and supported.